Sustaining competitive advantage via business intelligence, knowledge management, and system dynamics - Quaddus, M. A.; Woodside, Arch G. (Emerald, 2015)
The first chapter in this book examines the relationships between absorptive capacity and effective knowledge management through the analysis of quantitative data drawn from managers and employees in residential aged care organizations in Western Australia. The author, Michael Preece, defines absorptive capacity as the ability of an organization to use prior knowledge to recognize the value of new knowledge from external sources, assimilate this new knowledge, and apply it to the benefit of the organization. He provides valuable training in how service organizations go about transforming new knowledge into effective actionable business plans. The second chapter by Mohammad Shamsuddoha provides an application of system dynamics modelling in firms in the poultry industry in Bangladesh. This chapter offers deep knowledge of the "fifth discipline" and beyond. Shamsuddoha uses Vensim, a simulation-based software package, to build a simulation model with appropriate equations, formulae, and connectivity to replicate the real-life operation and outcome in a simulation environment. He also provides the in-depth knowledge necessary to learn to truly understand the fifth discipline.
Keywords: Business intelligence.; Knowledge management.; Competition.; elektronické knihy; electronic books